Professionalism in early childhood education and care : international perspectives - Dalli, Carmen; Urban, Mathias (London : Routledge, 2012)
The professionalism of the early childhood sector has gained prominence on the policy agendas of many countries. National pedagogical frameworks or curricula and an upsurge of pathways to gaining or upgrading qualifications has led to a pervasive terminology of professionalism. Yet, despite the pervasiveness of this terminology, the question of what professionalism means in early years contexts remains open to debate. This book draws together the work of an international group of scholars who have engaged with this question. They ask: How can professionalism be conceptualised in early childhood settings? How might one act professionally in increasingly diverse and changing social and cultural contexts? Do we have a common ground of understanding about these terms? Are there key concepts that can be agreed upon? Drawing on research and experience across a wide range of national contexts, this book seeks an understanding of early childhood professionalism in local contexts that might throw light on the global implications of this term.
Includes bibliographical references and index.
Keywords: Child care; Early childhood education; Professional employees